Colic incidence, risk factors, and therapeutic management in a working horse population in Tuban, Indonesia - Faisal Fikri; Dodit Hendrawan; Arya Pradana Wicaksono; Agus Purnomo; Shafia Khairani; Shekhar Chhetri; Muhammad Thohawi Elziyad Purnama; Hakan Çalışkan (Veterinary World, 2024)
Background and Aim: Colic is the primary problem affecting equestrian care worldwide. The primary cause of colic is digestive diseases; however, they can also affect organs from different systems in the abdominal region. In addition to a prior history of the disease and its treatment, risk factors may be assessed to determine the etiology of the disease in horses without or with a history of colic. This study aimed to present a summary of the incidence, risk factors, and medical procedures for colic in horses.